Pneumonias - Coelho, Liana Sousa [UNESP]; Do Vale, Simone Alves [UNESP]; Godoy, Irma de [UNESP]; Tanni, Suzana Erico [UNESP] (My University, 2012)
Pneumonia is an infectious disease with great morbidity and mortality worldwide. According to the current guidelines recommendations the authors reviewed the treatment of community-acquired pneumonia (CAP) and health care-associated pneumonia (HCAP). In this paper will be also presented data about etiology, clinics and diagnostic tools. © Copyright Moreira Jr. Editora.
Pneumonia
Keywords: Diagnostic; Pneumonia; Treatment; diagnostic test; pneumonia; review